Legislative Oversight of a Bill of Rights: A Way to Rectify Judicial Activism - Duane L. Ostler (Washington University Law Review, 2013)
The term ―judicial activism has become a common part of modern American political speech, though it remains ambiguous and can often mean many different things. It most commonly applies to judicial decisions that exceed judicial authority on issues that otherwise would be decided by the legislature and is most frequently invoked when some aspect of the bill of rights is litigated. Political leaders in both parties have condemned judicial activism, particularly where it threatens their party‘s ideology. For example, in 1968 Richard Nixon stated, "I want men on the Supreme Court who are strict constructionists, men that interpret the law and don‘t try to make the law." In 1986 Ronald Reagan said that America has "had too many examples in recent years of courts and judges legislating." Yet Democratic leaders can feel just as much concern for judicial activism as their Republican counterparts. Barack Obama expressed fear in 2012 that a conservative Supreme Court might disagree with the new healthcare law. This Article asserts that judicial activism does not have to be inevitable and can be overcome by way of structural change to the Constitution. Indeed, some of the founding fathers had just such a perspective. They preferred legislative oversight of rights issues, rather than risking judicial activism by leaving such matters to the judiciary.